Prejudice, marriage and motherhood: national and international perceptions on the 1938 prohibition of women in Brazilian foreign service - Tomas, Luah Batina (2020)
This Master\'s Thesis explores why women were perceived to be unsuited for diplomacy in Brazil during Getúlio Vargas\' Estado Novo dictatorship, particularly after an administrative reform in October 1938 prohibited women\'s access to the Brazilian Ministry of Foreign Relations. This decision stands out because women had already been allowed admittance into the Ministry starting in 1918, and female suffrage had just been granted in 1932. It also symbolizes a paramount change in Vargas\' government (1930-1945), which instated the so-called Estado Novo (New State) regime in 1937 after a coup d\'état. The objective is to uncover and comprehend the perceptions about gender of those against women\'s participation in diplomacy, which stimulated a sexual division of labor in civil service more broadly in which women\'s roles were limited to national, private, and supportive activities. The study interlaces primary documental sources from institutions and individuals connected to the 1938 decision, followed by a critical reading using feminist theories and gender as a category for historical analysis. The conclusion sees the Ministry\'s prohibition as part of two wider contexts: the ongoing process of rationalization of the Brazilian public administration that used entrance examinations as tools for implementing sexual divisions of labor; and the enabling conditions the government found in international diplomatic practices that presumed women\'s incapacity to obtain respect from peers, physical and emotional fragility, inability to discuss \"hard politics\", and a natural tendency for marriage and motherhood. The resulting understanding sheds light on collective meanings that helped shape norms of behavior and institutions with long-lasting impacts in Brazil\'s society - still today, only 23 per cent of the Brazilian diplomatic corps is composed of women.